2020
DOI: 10.1007/s00330-020-07315-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cone beam computed tomography is as reliable as conventional computed tomography for identification of pedicle screw breach in thoracolumbar spine surgery

Abstract: Objectives To test the hypothesis that intraoperative cone beam computed tomography (CBCT) using the Allura augmented reality surgical navigation (ARSN) system in a dedicated hybrid operating room (OR) matches computed tomography (CT) for identification of pedicle screw breach during spine surgery. Methods Twenty patients treated with spinal fixation surgery (260 screws) underwent intraoperative CBCT as well as conventional postoperative CT scans (median 12 months after surgery) to identify and grade the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
(66 reference statements)
1
24
0
1
Order By: Relevance
“…Post-operative CT was not performed because CBCT was considered sufficient for clinical evaluation [31].…”
Section: Methodsmentioning
confidence: 99%
“…Post-operative CT was not performed because CBCT was considered sufficient for clinical evaluation [31].…”
Section: Methodsmentioning
confidence: 99%
“…Comparing our results to the literature proved to be difficult as no studies were found reporting interrater agreement for two observers only. Burström et al reported an absolute interrater agreement between three observers of 72.9% for CT and 63.1% for CBCT, however, interrater reliability calculated as kappa was 0.48 for CT and 0.63 for CBCT which led the authors to draw the conclusion that CBCT is reliable to rule out pedicle perforation intraoperatively, making postoperative CT unnecessary 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, further studies demonstrated that intraoperative 3D imaging with a CBCT is not inferior to established computed tomography. The authors concluded that intraoperative CBCT could replace postoperative computed tomography after dorsal instrumentation in the future [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%